Chromatographic and spectral characteristic of some esters of a common monoterpene alcohols. (8th January 2016) - Bonikowski, Radosław; Paoli, Mathieu; Szymczak, Kamil; Krajewska, Agnieszka; Wajs‐Bonikowska, Anna; Tomi, Félix; Kalemba, Danuta
Abstract: Simple esters of monoterpene alcohols are common secondary plant metabolites for which there are no scientific reports that provide relevant information for identification of these compounds. The aim of this work was to create a database of monoterpene esters which made the identification of these constituents possible. 64 esters of common monoterpene alcohols were obtained. Retention indices, mass spectra and nuclear magnetic resonance data are given. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : 64 esters of common monoterpene alcohols were obtained. Retention indices, mass spectra and nuclear magnetic resonance data are given.